Historical Truth and Artistic Interpretation - Jabbor Eshonkulov (International Journal Of Literature And Languages, 2026)
The novel “Yaldo kechasi” represents one of the initial stages of the renewal process in Uzbek literature. In the work, the author presents not only a distinctive artistic attitude toward the past and reality, but also a broad artistic interpretation of the transformations in national spirit on the threshold of the 21st century, the stages of change in the worldview of the people, and the boundaries of spiritual maturity, covering more than a century of history. The novel stands out for its epic scope of reality, its unique artistic language, the clarity of its depiction, and the carefully developed characters and images. For this reason, it will continue to serve as a subject for many future studies. The article discusses the novel “Yaldo kechasi” by the People’s Writer of Uzbekistan Xayriddin Sulton, emphasizing that with its plot structure, interpretation of motifs and characters, and high artistic quality, it can be regarded as one of the works comparable with examples of world literature.